Pelaksanaan Sunat Perempuan dalam Perspektif Hukum Islam dan Kesehatan - Umi Salamah; Yaqut Elok Romlah Faiqoh; Salwaa ‘Aziizah; Lutfiyah Lutfiyah; Muhyar Fanani (STIKes Ibnu Sina Ajibarang, 2025)
Female circumcision, or female circumcision, is a practice that involves cutting off part or all of a woman's external genital organs. This practice is often a topic of debate in the context of Islamic law and health. This article aims to examine the implementation of female circumcision from two main perspectives: Islamic law and health by using a qualitative descriptive approach with library research methods to examine various related literature. In the results of research on the implementation of female circumcision from the perspective of Islamic law and health, it is explained that the implementation of female circumcision is interpreted with various interpretations in fiqh literature, where there are different views among scholars regarding whether the law is mandatory, sunnah, or not recommended at all. On the health side, female circumcision is often associated with medical risks and long-term impacts on women's physical and psychological health, including potential complications of infection, pain, and psychological impacts such as trauma.